Influência do índice de vegetação por diferença normalizada (NDVI) sobre a carga de sólidos suspensos do arroio Fundo-Paraná - Kaiser, Eduardo Andre (2018)
From the prior knowledge of the physical characteristics of terrestrial and aquatic environments as well as their relationships, it becomes possible to maintain, recover and properly conserve water resources, and thus the aquatic ecosystem. The present study aims to analyze the influence of Normalized Difference Vegetation Index (NDVI) of the watershed on the suspended solids load of Arroio Fundo in the State of Paraná. For this, statistical techniques of determination and correlation of data from field sampling and remote orbital sensing were used. The methodology included the following procedures: a) characterization of the rainfall on 30 days accumulated before the dates of collection of Suspended Solids Totals (TSS); b) elaboration of average monthly NDVI maps of the watershed with the use of satellite images.; c) acquisition of sedimentometric data from station E16A5-00 located in Arroio Fundo, Paraná, and; d) observation of the relationship NDVI of the watershed and TSS of the Arroio Fundo water in front of the rain events from the performance of the Coefficients of Determination and Correlation. The results pointed to different effects on the amount of material suspended in the Arroio Fundo water, as opposed to variations in the agricultural calendar characterized by the NDVI and the rainfall (seasonal) volumes incident in the watershed. The greatest influence of the vegetation index on the amount of TSS in the river occurred when the areas with low NDVI (surface exposure) predominated in the basin whose R² between rainfall and TSS was 0.58. Considering the characterization of the high NDVI (presence of vegetation cover) of the watershed, no significant coefficient of determination between rainfall and TSS of water was obtained, whose R² resulted in 0.13 Due to the variations in the agricultural calendar, from September to November the maximum contribution of the surface exposure areas to the increment of TSS in Arroio Fundo water was verified, while in the period from March to May the predominance of temporary crops on the basin characterized the minimal contribution. In general, the TSS concentration of Arroio Fundo responded to the effect of rainfall on the surface of the watershed. However, the influence of NDVI on this effect can be verified in a different way according to two perspectives: the predominance of agricultural coverages and absence of these marked by surface exposure.